Er3+-doped niobium alkali germanate glasses and glass-ceramics: NIR and visible luminescence properties - Marcondes, Lia Mara; Evangelista, Renato Oliveira; Goncalves, Rogeria Rocha; Camargo, Andrea S. S. de; Manzani, Danilo; Nalin, Marcelo [UNESP]; Cassanjes, Fabia Castro; Poirier, Gael Yves (Elsevier B.V., 2019)
Niobium alkali germanate glasses doped with Er3+ up to 4.0 mol% were synthesized by the melt-quenching technique. Glass-ceramics were obtained by controlled heat treatment of the pristine glass. Thermal and optical properties were investigated and are shown to depend on the erbium content. The main radiative parameters were obtained based on the Judd-Ofelt theory. The change of radiation energy processes and modification of the environment of the earth-rare ion occurs in samples with high erbium concentrations. In general, strong enhancement of upconversion emission occurs due to the efficient process of excited-state absorption for the high erbium content samples. Visible tunable phosphors emitting either red-to-green light depends on the erbium content and heat treatment. In addition, these glasses and glass-ceramics samples have high thermal stability and wide transmission window. For these reasons, Er3+-doped niobium germanate glasses and glass-ceramics may be suitable for photonic device applications, especially as visible laser.
Keywords: Luminescence; Glass; Glass-ceramics; Erbium; Concentration quenching